АВТОРСКИЕ КОДЫ МАРИНЫ ЦВЕТАЕВОЙ В СИМВОЛИКЕ ЛЮТНИ - Fokina, Swietłana (Przegląd Rusycystyczny, 2014)
Swietłana Fokina Одесский национальный университет имени И.И. Мечникова, Odessa, Ukraine svetlana_fokina@ukr.net AUTORSKIE KODY MARINY CWIETAJEWEJ W SYMBOLICE LUTNI Streszczenie Przedmiotem artykułu jest wpływ autorskich kodów na specyfikę symboliki lutni w wierszu Mariny Cwietajewej Lutnia. AUTHORIAL CODES OF MARINA TSVETAEVA IN SIMBOLITY OF LUTE Summary In the article attention is concentrated on the comprehension of influence of authorial codes on the specific of symbolity of lute on material of the same name poem of M. Tsvetaeva.